HARMONISASI NORMA HUKUM BAGI PERLINDUNGAN HAK KEPERDATAAN ANAK LUAR KAWIN DALAM SISTEM HUKUM INDONESIA - Resti Nurhayati, Bernadeta (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
Communities and laws have long discriminated against children outside of marriage. This causes out of wedlock children to get a negative stigma in their daily lives. People call it with various terms such as: â€œanak haramâ€, â€œharam jadahâ€, â€œanak kowarâ€, â€œanak astralâ€ and so on. Until now Indonesian law distinguishes the status, position and rights of children out of wedlock. An urgent issue to be resolved is disharmony in written legal norms that regulate the protection of children outside of marriage. The research objective is to evaluate and harmonize the legal norms that exist in the field of protection of civil rights of non-married children. Harmonization of these legal norms is based on the practice of legal protection, doctrine, and written norms that are directly related to the protection of extramarital children in Indonesia. This research is a complement to the dissertation. In this research, an inventory of positive legal norms in the field of status and position of out-of-child children, legal practices relating to the protection of children outside of marriage and the relevant legal theory to see the possibility of protection of children's rights. In this research, mapping of norms and institutions will be conducted to find out the parts that are conflicting / incompatible with each other, as a basis for formulating harmonization of laws and regulations in the field of status and position of children outside of marriage. From this harmonization, it is expected that norms that need to be revised will be found and formulas for norms that provide protection for civil rights for married children in Indonesia. Outputs are in the form of: draft dissertations that have been approved by promoters, reputable international scientific publications, accredited national publications, speakers of national and international meetings, and additional outputs in the form of draft reference books.